Plate 04. View of Elfeld and Erbach - Janscha, Laurens, 1749-1812 (artist):::::::::::::::; Ziegler, Johann (engraver)::::::::::::::: (United Kingdom; Paul Harris; Edinburgh, 2020)
Color engraving with a view of the villages of Eltville and Erbach in Germany, from across the Rhine. Elfeld (Eltville) is a particularly ancient town, with traces of habitation dating back to the New Stone Age. It was the residence of the Electors of Mainz, one of whom (Dietrich Schenk von Erbach) lent his name to the nearby village.